The Temporal and Spatial Changes of Health Inequality in Rural China - Jiang, Jinqi; Huang, Wanzhen; Liu, Yunru; Wang, Zhenhua (Frontiers in Public Health, 2022)
This article estimates the temporal and spatial changes of health inequality in rural China from 2010 to 2018. Based on a panel database of 29,616 rural residents, the Health Utility Index (HUI) and a spatial econometric model are used for analysis. The results show that, on the temporal dimension, the health inequality of rural China first expands and then deflates. On the spatial dimension, the health inequality gradually deflates from eastern to western China. Furthermore, from 2010 to 2018, the high and low-value areas constantly changed among different provinces. After decomposing the causes of health inequality, it is found that behind the health inequality is the difference of socioeconomic-related status. Moreover, narrowing the difference in socioeconomic-related status is the key to improving health inequality.